2018
DOI: 10.1097/md.0000000000011558
|View full text |Cite
|
Sign up to set email alerts
|

Association between rs1800795 polymorphism in the interleukin-6 gene and the risk of polycystic ovary syndrome

Abstract: Objective:Several published articles have investigated the association between the −174 G/C (rs1800795) polymorphism in the interleukin-6 (IL-6) gene and the risk of polycystic ovary syndrome (PCOS). However, the results were inconsistent. In the present study, a meta-analysis was performed to resolve this inconsistency.Methods:Eligible studies reporting an association between the IL-6 rs1800795 polymorphism and PCOS susceptibility were included from PubMed, Embase, Web of Science, and the Cochrane Library up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 31 publications
(38 reference statements)
0
16
0
1
Order By: Relevance
“…All 21 systematic reviews included a meta-analysis and were based on case-control or cross-sectional primary studies. Nineteen systematic reviews investigated SNPs [33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51]. The remaining two systematic reviews investigated CAG repeat length or tandem repeats respectively [52,53].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All 21 systematic reviews included a meta-analysis and were based on case-control or cross-sectional primary studies. Nineteen systematic reviews investigated SNPs [33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51]. The remaining two systematic reviews investigated CAG repeat length or tandem repeats respectively [52,53].…”
Section: Resultsmentioning
confidence: 99%
“…The remaining two systematic reviews investigated CAG repeat length or tandem repeats respectively [52,53]. Candidate genes focused on three main aspects of PCOS pathophysiology: metabolic dysfunction, [33,35,38,39,40,41,42,43,44,48,49,50,52], imbalances in androgens and gonadotrophins [36,37,51,53], and inflammation [34,45,46,47].…”
Section: Resultsmentioning
confidence: 99%
“…The meta-analysis from Zhou et al revealed a non-significant association between the IL-6 -174 G/C polymorphism and overall cancer risk [ 17 ]. On the other hand, Chen et al found that the IL-6 -174 G/C polymorphism protected against polycystic ovary syndrome [ 18 ]. And Duan et al reported that the -174 G/C polymorphism was a low-penetrance susceptibility variant for cervical cancer [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association between IL-6 rs1800795 polymorphism and disease risk such as cervical cancer [18]; polycystic ovary syndrome [19]; type 2 diabetes [20] and rheumatoid arthritis [21], has been widely investigated. Similarly, IL-6 rs1800797 polymorphism has also been studied in various disease [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%